Religious Syimbols and the Maintenance of Social harmony in Lombok, West Nusa Tenggara - Muhtar, Fathurrahman (FIKRAH, 2021)
Symbols have been a crucial part of all religions in the world for they can represent religious values, ideas, and events. This study seeks to examine the meaning of religious symbols in Lombok, West Nusa Tenggara, and their role in maintaining socio-religious harmony in the region. Qualitative and interpretative in nature, data collection techniques in this study were carried out through interviews, observation, and documentation. Meanwhile, data analysis employed a grounded theory design. The results of this study indicate that the symbols of religious pluralism are visible on the Pura Meru (next to the Nurul Falah mosque), on the statues of various religious figures at the Pura Mayura, and on the Pura Lingsar, a home for an ancient building called Kemalik. These symbols have been recognized as common properties of Hindus and Muslims and as places to get blessings. There is also the Topat War festival which is a legacy of Muslim and Hindu traditions used as a medium to pour out any form of anger among religious adherents and then end with peace. Those symbols are believed to be able to foster togetherness and harmony in Lombok, West Nusa Tenggara. In general, these religious symbols have made Cakranegara and Lingsar peaceful areas free from religious conflicts to date.